The challenges towards implementation of sustainable housing in Ipoh, Perak / Nur Afiqah Hafizul and Mohd Hasrol Haffiz Aliasak - Hafizul, Nur Afiqah; Aliasak, Mohd Hasrol Haffiz (2019)
Uncontrolled development in housing growth brings negative impact to the environment. Therefore, the concept of sustainable development was introduced to curb uncontrolled development. This research aims to identify the challenges of the developer and to determine the best way to encourage them to implementing the sustainable development in housing scheme project. Data was collected by the literature review and questionnaire. The questionnaire was disturbed among the developer who were randomly selected that operating in Ipoh, Perak. Then, the data was analyzed by SPSS version 19. This research found that the level of the awareness and understanding on the sustainable development among the developer is moderate level. However, it shows majority of respondents ranked the lack of demands from homebuyer as the most challenges to implementation the sustainable development in housing scheme project. Therefore, more effort from the government and private sectors is necessary to boost this application and further stimulate action and strategies towards the sustainable development.